The Effectiveness Of Problem-Based Learning and Project-Based Learning in Enhancing Critical and Creative Thinking in Geometry Transformation for Class IX - Ardiana Purnamasari; Atmini Dhoruri (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
This study aims to describe the effectiveness of the Problem Based Learning (PBL) and Project Based Learning (PjBL) models in the context of Batik Purworejo, particularly regarding the critical and creative thinking abilities of junior high school students. This research is a quasi-experimental study involving the population of ninth-grade students at SMP Negeri 2 Purworejo for the 2023/2024 academic year. Samples were randomly selected from two classes, IX A using PjBL and IX B using PBL. The research instruments consisted of validated tests to measure students' critical and creative thinking abilities. Data analysis was performed using the One Sample t-test for PBL and N-Gain for PjBL, as well as the Wilcoxon Signed Rank test to compare the two models. The results indicated that the PBL model is effective in enhancing critical thinking, while PjBL also proves effective in the same aspect. However, the PBL model was not effective in improving creative thinking, whereas PjBL was found to be effective. Additionally, PjBL was more effective than PBL in enhancing critical thinking, although both models did not show significant differences in improving creative thinking abilities.